SpRY: Engineered CRISPR/Cas9 Harnesses New Genome-Editing Power. Issue 8 (August 2020) - Zhang, Dangquan; Zhang, Baohong
Abstract : Due to protospacer adjacent motif (PAM) requirements, CRISPR/Cas9 cannot access many genetic loci. A recent study by Walton et al. structurally engineered Streptococcus pyogenes Cas9 (SpCas9) to near-PAMless SpRY that can target most DNA sequences with high editing efficiency and flexibility. This newly engineered SpRY will potentially expand genome-editing capabilities for basic and applied research.